2007
DOI: 10.1152/ajpheart.01303.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 mitogen-activated protein kinase pathway in estrogen-mediated cardioprotection following trauma-hemorrhage

Abstract: IH. Role of p38 mitogenactivated protein kinase pathway in estrogen-mediated cardioprotection following trauma-hemorrhage. Am J Physiol Heart Circ Physiol 292: H2982-H2987, 2007. First published February 9, 2007 doi:10.1152/ajpheart.01303.2006.-p38 mitogen-activated protein kinase (MAPK) activates a number of heat shock proteins (HSPs), including HSP27 and ␣ B-crystallin, in response to stress. Activation of HSP27 or ␣ B-crystallin is known to protect organs/cells by increasing the stability of actin microfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 48 publications
6
47
1
Order By: Relevance
“…However, it was reported that after traumatic bleeding, up-regulation of p38 MAPK signaling pathway can activate heat shock protein such as HSP27 and a B-crystallin by phosphorylation, and induces the cell protective effect of the body [23]. In addition, activation of p38 MAPK is associated with wound healing because p38 MAPK influences the motions of many types of cells that take an important part in the healing process, such as immune cells, fibroblasts, epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that after traumatic bleeding, up-regulation of p38 MAPK signaling pathway can activate heat shock protein such as HSP27 and a B-crystallin by phosphorylation, and induces the cell protective effect of the body [23]. In addition, activation of p38 MAPK is associated with wound healing because p38 MAPK influences the motions of many types of cells that take an important part in the healing process, such as immune cells, fibroblasts, epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed in adherence with National Institutes of Health (Bethesda, MD) Guidelines for the Care and Use of Laboratory Animals and approved by the Institutional Animal Care and Use Committee of the University of Alabama at Birmingham. A nonheparinized model of trauma-hemorrhage was used as described previously (1,31). Briefly, rats were anesthetized by isoflurane inhalation before the induction of soft tissue trauma via 5-cm midline laparotomy.…”
Section: Rat Trauma-hemorrhagic Shock Modelmentioning
confidence: 99%
“…In this regard, we have found that cardiac function is depressed in male animals and ovariectomized females but not in proestrus females, a state with the highest plasma levels of 17␤-estradiol (E2) following trauma-hemorrhage (31)(32)(33)(34). Additional findings have indicated that precastration of males resulted in normalization of cardiac function following trauma-hemorrhage (1).…”
mentioning
confidence: 99%
“…These effects were not seen during other phases of the estrus cycle, when estrogen levels are lower (26,27). E2 supplementation in ovariectomized females and male rats attenuated the depressed cardiovascular function associated with trauma-hemorrhage through activation of p38 MAPK and PI3-K/AKT (28,29).…”
Section: Estrogen and Sex Differences In Cardiovascular Diseasementioning
confidence: 91%
“…In addition, E2 stimulates the phosphorylation of HSP 27 and αβ-crystallin via p38 MAP kinase, essential for the protective properties of these proteins (28). Further evidence of E2 increasing expression of HSPs are the observations that intact females have higher levels of HSP 72 than males, both basally and following ischemia/reperfusion, in cardiac and renal tissue (95,98).…”
Section: E2 and Heat Shock Protein Expressionmentioning
confidence: 99%